1994
DOI: 10.1038/368348a0
|View full text |Cite
|
Sign up to set email alerts
|

Opposite voltage gating polarities of two closely related onnexins

Abstract: The molecular mechanisms underlying the voltage dependence of intercellular channels formed by the family of vertebrate gap junction proteins (connexins) are unknown. All vertebrate gap junctions are sensitive to the voltage difference between the cells, defined as the transjunctional voltage, Vj (refs 1, 2), and most appear to gate by the separate actions of their component hemichannels. The heterotypic Cx32/Cx26 junction displays an unpredicted rectification that was reported to represent a novel Vj dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
358
2
2

Year Published

1996
1996
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 336 publications
(383 citation statements)
references
References 25 publications
21
358
2
2
Order By: Relevance
“…Most simply, the extracellular region of the hemichannel when it is at the substate conductance could have a very different configuration to that of the same region in the cell-cell channel. V j or fast gating to the substate in cell-cell channels is thought to involve the cytoplasmic end of the channel, and charges implicated in the voltage sensor are located there; however, other charged residues affecting gating are found at the beginning of the first extracellular loop [45,50].…”
Section: What Opens Hemichannels?mentioning
confidence: 99%
See 1 more Smart Citation
“…Most simply, the extracellular region of the hemichannel when it is at the substate conductance could have a very different configuration to that of the same region in the cell-cell channel. V j or fast gating to the substate in cell-cell channels is thought to involve the cytoplasmic end of the channel, and charges implicated in the voltage sensor are located there; however, other charged residues affecting gating are found at the beginning of the first extracellular loop [45,50].…”
Section: What Opens Hemichannels?mentioning
confidence: 99%
“…Most simply, the extracellular region of the hemichannel when it is at the substate conductance could have a very different configuration to that of the same region in the cell-cell channel. V j or fast gating to the substate in cell-cell channels is thought to involve the cytoplasmic end of the channel, and charges implicated in the voltage sensor are located there; however, other charged residues affecting gating are found at the beginning of the first extracellular loop [45,50].Although not yet adequately characterized, there are differences in singlechannel rectification in hemichannels. An open hemichannel could well exhibit asymmetry in fixed charges that causes rectification, whereas the asymmetry is neutralized in the cell-cell channel [45,51].…”
mentioning
confidence: 99%
“…Studies of Cx40 [36] and Cx56 [37] also suggested that NT residues were involved in both voltage sensing and pore properties. Interestingly, mutations at the M1/E1 border in Cx32 also affected the polarity of voltage sensitivity [31] and in Cx56 altered voltage gating [37]. These data implicate the two extramembrane segments on either end of M1 as involved in the pore, and inspired a set of domain swaps, point mutations, and studies using the substituted cysteine accessibility method (SCAM) on this and other regions.…”
Section: The Connexon Contains a Ring Of 24 α-Helicesmentioning
confidence: 89%
“…Their work showed that single amino acid charge changes in the ostensibly cytoplasmic, amino-terminal (NT) domain of a Cx32 variant could actually reverse the polarity of voltage that caused the channels to close [31][32][33][34]. NMR spectroscopy of an NT peptide suggested that it could adopt a bent conformation allowing NT amino acids to access the cytoplasmic vestibule of the pore [35].…”
Section: The Connexon Contains a Ring Of 24 α-Helicesmentioning
confidence: 99%
“…The W residue at codon 4 is highly conservative among species, and the mutation is predicted to impair Cx50 protein function. Moreover, the N-terminal domain of connexin was reported to influence transjunctional voltage-dependent gating (Verselis et al 1994;Oh et al 2000), channel conductance (Musa et al 2004), and permeability (Dong et al 2006). A reported cataract pathogenic mutant CX50 R23T impaired trafficking and formation of gap junction, which might be caused by the replacement of the positively charged amino acid R with an uncharged, polar amino acid Threonine (T) (Thomas et al 2008).…”
Section: Discussionmentioning
confidence: 99%